Sistem Pakar Diagnosa Penyakit Kucing Menggunakan Metode Forward Chaining Berbasis Web - Izdihar Thallah; Elfi Fauziah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
A domesticated animal could be classified as easy the maintenance one of the ways is one was kittens. But to keep cats well cared for is not easy. Most cats with the disease don't look that sick. Cat owners sometimes only realize when their pet cat experiences significant changes such as hair loss to baldness, reddish skin and even wounds. The purpose of this study is to diagnose cat diseases as a first step to apply artificial intelligence in the medical world, to design and apply an expert system capable of diagnosing cat diseases. So the authors created a web-based expert system application to diagnose cat diseases accompanied by healing therapies and how to treat them. The method used in this study is forward chaining, namely tracking that starts from input information, and then tries to draw conclusions. This research will produce a web-based application for diagnosing cat diseases.